On the devitrification of Cu–Zr–Al alloys: Solving the apparent contradiction between polymorphic liquid-liquid transition and phase separation. (March 2022) - Jiang, Hao-Ran; Tseng, Jochi; Neuber, Nico; Barrirero, Jenifer; Adam, Bastian; Frey, Maximilian; Dippel, Ann-Christin; Banerjee, Soham; Gallino, Isabella; Feng, Ai-Han; Wang, Gang; Mücklich, Frank; et al.
Abstract: In this work, the crystallization pathways and kinetics of the Cu47.5 Zr45.1 Al7.4 bulk metallic glass (BMG) are studied systematically using a broad collection of laboratory and synchrotron-based techniques, such as differential scanning calorimetry, transmission electron microscopy, in situ high-energy synchrotron X-ray diffraction (HEXRD), simultaneous small- and wide-angle X-ray scattering, and atom probe tomography. The crystallization sequence during heating at conventional slow rates and isothermal annealing near the glass transition temperature was determined to consist in preferential formation of (Cu, Al)10 Zr7 followed by the formation of CuZr2 and AlCu2 Zr induced by long-range atomic diffusion. In situ HEXRD shows that the formation of the latter two phases is accompanied by the partial dissolution of the primary Cu-rich phase. Microstructural characterizations of annealed samples suggest that a new liquid phase with enhanced local order and obscure compositional changes has formed from the homogeneous supercooled liquid before crystallization. A concept analogous to the disorder-to-order transition in crystalline materials is applied here to describe the observed transition in liquid, resolving the longstanding apparent contradiction between observing a nanoscale phase separation versus a liquid–liquid phase transition during devitrification. Furthermore, we suggest that the formation of an intermediate liquid phase prior to crystallization is the structural origin of the rapid devitrification kinetics during the primary crystallization. On the basis of our combined experimental results, a scheme is proposed to generalize the complex multistep devitrification mechanisms of the Cu47.5 Zr45.1 Al7.4 BMG during isothermal annealing or slow heating. This work may provide new insights into the crystallization behavior and thermal stability of Cu–Zr–Al BMGs in terms of thermodynamics and kinetics and might lead to deeper understanding of the underlying mechanisms of the often observed rapid crystallization processes of deeply undercooled metallic liquids. Graphical Abstract: Graphical Abstract Image, graphical abstract .